Teknologi Virtual Reality pada Media Pembelajaran Proses Pemasangan Kabel UTP Cross dan Straight - Taufik Gusman; Muhammad Umar Huzein (SOTVI - Society of Visual Informatics, 2022)
Virtual Reality is an engineering technology that aims to create simulations that are similar to reality. Virtual Reality is widely used for game development and education purposes. In the field of education, Virtual Reality is usually used as an alternative source of learning a material. Like an imitation of the digestive tract, students can learn the intricacies of the material being studied easily. The application of the cross and straight UTP cable installation process aims to facilitate the learning of Information Technology Department students who are still conducting online lectures and is used to make it easier for students to understand how to make straight and cross Local Area Network cables. Making this application using the Unity3D application, which is an application used to create applications or games based on virtual reality and augmented reality. For the manufacture of the models that will be used, made using the blender application. This Virtual Reality application will run on Google Carboard using an Android smartphone